Prison and Freedom in Nadia Hashimi’s A House Without Windows - Putratama, Muhammad Raihansyah; Chusna, Inayatul (UIN Syarif Hidayatullah Jakarta, 2022)
This research aims to analyse a prison where the characters achieve their freedom, while outside the prison they get oppressed by the men. This research uses the freedom concept by Jean-Paul Sartre because of the relevancy behind the theory and the story. The corpus of this research is Nadia Hashimi’s A House Without Windows (2016). The study uses the existentialism theories from Jean-Paul Sartre and Representation theory by Stuart Hall to support the analysis. The result of this research shows a great contrast between the women when they were out of prison and when they were in prison. Outside the prison, they continue to experience oppression from various parties, while when they are in prison, they live more freely than when they were outside the prison. For the inmate, the definition of freedom itself shifts from the common definition. To be able to get freedom is not only in an open space, but it can also be in a prison where the space for movement is limited, but not by their actions and speech.